2022
DOI: 10.3389/fonc.2022.821391
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of SKI-G-801, a Novel AXL Inhibitor, With Anti-PD-1 Plus Chemotherapy Improves Anti-Tumor Activity and Survival by Enhancing T Cell Immunity

Abstract: A recently developed treatment strategy for lung cancer that combines immune checkpoint inhibitors with chemotherapy has been applied as a standard treatment for lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), and it has improved the outcomes of chemotherapy. Maintenance treatment with anti-PD-1 antibody (aPD-1) enhances the effect of immunochemical combination therapy and improves therapeutic efficacy, which contributes toward a significant improvement in patient survival rates. The AXL re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In vivo pharmacologic inhibiting pan-TAM Tyrosine Kinases, TYRO3, AXL, and MERTK, diminishes MDSC suppressive capability, promotes CD8 + T cell infiltration, slows tumor growth, and augments anti-PD-1 immunotherapy [ 247 249 ]. Consistently, another AXL kinase inhibitor, SKI-G-801, blocks metastasis through inducing anti-tumor immune responses and potentiates anti-PD-1 therapy in multiple mouse cancer models (including B16F10 melanoma, CT26 colon, 4T1 breast, TC1 and C3PQ lung cancer models) [ 250 , 251 ]. Similarly, combining AXL kinase inhibitor R428 with anti–PD-1 in a mouse HER2 + breast cancer model reduces the primary tumor and metastatic burdens [ 171 ].…”
Section: Potential Strategies Targeting Emp To Enhance the Icb Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In vivo pharmacologic inhibiting pan-TAM Tyrosine Kinases, TYRO3, AXL, and MERTK, diminishes MDSC suppressive capability, promotes CD8 + T cell infiltration, slows tumor growth, and augments anti-PD-1 immunotherapy [ 247 249 ]. Consistently, another AXL kinase inhibitor, SKI-G-801, blocks metastasis through inducing anti-tumor immune responses and potentiates anti-PD-1 therapy in multiple mouse cancer models (including B16F10 melanoma, CT26 colon, 4T1 breast, TC1 and C3PQ lung cancer models) [ 250 , 251 ]. Similarly, combining AXL kinase inhibitor R428 with anti–PD-1 in a mouse HER2 + breast cancer model reduces the primary tumor and metastatic burdens [ 171 ].…”
Section: Potential Strategies Targeting Emp To Enhance the Icb Responsementioning
confidence: 99%
“… [ 246 ] BMS-777607 Murine Model of Triple-Negative Breast Cancer Blocks macrophage efferocytosis and Gas6-PS–opsonized apoptotic cell, and enhances anti-PD-1 mAb efficacy via up-regulating PD-L1 expression [ 249 ] SKI-G-801 B16F10 melanoma, CT26 colon and 4T1 breast model Blocks metastasis through inducing CD8 + T cells, decreasing M2 macrophage and potentiates anti-PD-1 therapy [ 250 ] TC1 and C3PQ mouse tumor models Improves efficiency of anti-PD-1 therapy, exhibiting increased proportion of effector memory helper T cells, CD86+ macrophages. [ 251 ] Enapotamab vedotin (EnaV) Melanoma and lung cancer models Induced ICB benefit and promoted the induction of a memory-like phenotype in cytotoxic T cells. [ 252 ] R428 HER2 + breast cancer Enhances anti-PD-1 responses via increased CD8 + T cells [ 171 ] PDGFR inhibitors Imatinib Gastrointestinal stromal tumors Abrogated the IFN-γ induced upregulation of PD-L1 via STAT1 inhibition.…”
Section: Potential Strategies Targeting Emp To Enhance the Icb Responsementioning
confidence: 99%
“…Vimentin contributes to the stabilization of focal adhesion kinase, 9 which inhibits CD8 + cellular infiltration and induces T regulatory cell infiltration 43 . Vimentin is also associated with inducing expression of Axl receptor tyrosine kinase, 7,10 which decreases the efficacy of ICI 44,45 . These mechanisms may adversely affect ICI treatment and may be partially related to the poor efficacy of ICI in the vimentin highly positive group (≥50%) in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…43 Vimentin is also associated with inducing expression of Axl receptor tyrosine kinase, 7,10 which decreases the efficacy of ICI. 44,45 These mechanisms may adversely affect ICI treatment and may be partially related to the poor efficacy of ICI in the vimentin highly positive group (≥50%)…”
Section: -Vimentin and Immune-checkpoint Inhibitormentioning
confidence: 99%
“…A recent mouse study demonstrated that AXL inhibitors impact the immune status and tumor growth in lung cancer. Application of AXL inhibitors to treat mice resulted in delayed tumor growth, elevated rate of effector memory helper T cells, enhanced infiltration of central memory cytotoxic T cells, increased amounts of CD86+ macrophages, and elevated proportion of CD80 high-expression macrophages in the tumor model ( 113 ).…”
Section: Role Of Gas6/axl In the Tmementioning
confidence: 99%